Respuesta :

№7

[tex]4(5y - 2) = 52\\4*5*y - 4 * 2 = 52\\20y - 8 = 52\\20 y = 52 + 8\\20y = 60\\y = 60 : 20\\y = 3[/tex]

№11

[tex]2x + 17 = 5x - 4\\17 + 4 = 5x - 2x\\21 = 3x\\x = 21 : 3\\x = 7[/tex]

№12

[tex]2x + 7 = 16 - 4x\\2x + 4x = 16 - 7\\6x = 9\\x = 9 : 6\\x = \frac{3}{2}\\x = 1,5[/tex]

№14

[tex]4(2y + 1) = 2 (12 - y)\\4*2*y + 4 * 1 = 2 * 12 - 2 * y\\8y + 4 = 24 - 2y\\8y + 2y = 24 - 4\\10y = 20\\y = 20 : 10\\y = 2[/tex]

№15

[tex]7 - 3x = 2(x + 1)\\7 - 3x = 2x + 2\\7 - 2 = 2x + 3x\\5 = 5x\\x = 5 : 5\\x = 1[/tex]

№16

[tex]\frac{x-3}{2} = 5\\x-3 = 5*2\\x - 3 = 10\\x = 10 + 3\\x = 13[/tex]

ACCESS MORE